Constitutively expressed Protocadherin-α regulates the coalescence and elimination of homotypic olfactory axons through its cytoplasmic region - Hasegawa, Sonoko; Hirabayashi, Takahiro; Kondo, Takahiko; Inoue, Ken; Esumi, Shigeyuki; Okayama, Atsushi; Hamada, Shun; Yagi, Takeshi (Frontiers in Molecular Neuroscience, 2012)
Olfactory sensory neuron (OSN) axons coalesce into specific glomeruli in the olfactory bulb (OB) according to their odorant receptor (OR) expression. Several guidance molecules enhance the coalescence of homotypic OSN projections, in an OR-specific- and neural-activity-dependent manner. However, the mechanism by which homotypic OSN axons are organized into glomeruli is unsolved. We previously reported that the clustered protocadherin-α (Pcdh-α) family of diverse cadherin-related molecules plays roles in the coalescence and elimination of homotypic OSN axons throughout development. Here we showed that the elimination of small ectopic homotypic glomeruli required the constitutive expression of a Pcdh-α isoform and Pcdh-α's cytoplasmic region, but not OR specificity or neural activity. These results suggest that Pcdh-α proteins provide a cytoplasmic signal to regulate repulsive activity for homotypic OSN axons independently of OR expression and neural activity. The counterbalancing effect of Pcdh-α proteins for the axonal coalescence mechanisms mediated by other olfactory guidance molecules indicate a possible mechanism for the organization of homotypic OSN axons into glomeruli during development.